LEGAL NATURE AND LIMITS OF LAWYER‘S SECRECY UNDER THE LEGISLATION OF UKRAINE - Заборовский, Виктор Викторович Викторович (Teisė, 2017)
Article is devoted to the legal nature the legal nature and limits of the legal secret under Ukrainian law. Particular attention is paid to clarifying regulatory regulations and the positions of scientists about possible cases of disclosure of information containing a lawyer‘s secret. It is concluded that the possibility of disclosing such information should be determined only by the interests of the client (on his written application), and also in the case of his presentation of claims to a lawyer in connection with the professional activities of the latter.